Current Situation and Application of PMSM Driver System - GUO Shu-ying (机车电传动)
Classification and current researching situation of PMSM was reviewed. Characteristics and shortages of PMSM wereanalyzed, and situation and focus of PMSM control technology was introduced in emphasis. Application field and development trend ofPMSM driver system was discussed, and a viewpoint was carried out that PMSM direct-driving system was the development trend ofPMSM driver system, which exploited the ultimate advantaged of PMSM.